2010
DOI: 10.1080/02791072.2010.10399782
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Effects of Marijuana on Simulated Driving Performance

Abstract: In the United States, one in six teenagers has driven under the influence of marijuana. Driving under the influence of marijuana and alcohol is equally prevalent, despite the fact that marijuana use is less common than alcohol use. Much of the research examining the effects of marijuana on driving performance was conducted in the 1970s and led to equivocal findings. During that time, few studies included women and driving simulators were rudimentary. Further, the potency of marijuana commonly used recreational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 46 publications
(50 reference statements)
3
67
1
Order By: Relevance
“…According to a recent review, drivers who used marijuana compensate by driving slower; however, their control deteriorates with increasing task complexity (Hartman and Huestis, 2013). Marijuana use increases lane weaving, decreases mean speed, increases mean and variability in headways, and impairs cognitive function, critical tracking tests, reaction times, divided attention tasks, expected practice effects, and lane position variability (Anderson et al, 2010; Downey et al, 2013; Hartman and Huestis, 2013; Lenne et al, 2010). The increased risk of impaired driving skills occurs for both lower and higher levels of delta-9-tetrahydrocannabinol (THC) concentrations (Bramness et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent review, drivers who used marijuana compensate by driving slower; however, their control deteriorates with increasing task complexity (Hartman and Huestis, 2013). Marijuana use increases lane weaving, decreases mean speed, increases mean and variability in headways, and impairs cognitive function, critical tracking tests, reaction times, divided attention tasks, expected practice effects, and lane position variability (Anderson et al, 2010; Downey et al, 2013; Hartman and Huestis, 2013; Lenne et al, 2010). The increased risk of impaired driving skills occurs for both lower and higher levels of delta-9-tetrahydrocannabinol (THC) concentrations (Bramness et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Lenné et al (2010) also analyzed effects by dose rather than concentration, possibly resulting in greater apparent effect size because dose-wise (categorical) variable analyses generally have higher power than continuous variables. Multiple other studies found no cannabis-only effect on steering wheel position variability (Anderson et al, 2010; Ronen et al, 2010), although one observed increased steering variability in occasional smokers after alcohol alone and alcohol-cannabis combination (Ronen et al, 2010). Standard deviation of steering angle appears insensitive, due to the amplifying effect of steering mechanisms.…”
Section: Discussionmentioning
confidence: 94%
“…Lane weaving, an observable effect of drug-impaired driving, is a common measure for assessing driving performance. Standard deviation of lateral position (SDLP) is a sensitive vehicular control indicator, often employed in drugged driving research (Anderson et al, 2010; Lenné et al, 2010; Ramaekers et al, 2006a; Verster et al, 2006). In previous studies, cannabis increased SDLP and straddling lanes, but results were assessed by dose rather than blood THC concentrations (Ramaekers et al, 2000; Robbe, 1998; Downey et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the United States, males are more likely to use the emergently popular, synthetic cannabinoid formulation K2 (a.k.a., spice) than women (Hu et al, 2011). By contrast, no sex differences were reported for cannabis -induced impairment in simulated driving performance (Anderson et al, 2010). In addition, women appear to be more sensitive to cannabinoidinduced exacerbation of the postural syncope associated with the transition from the reclined to the standing position (Mathew et al, 2003).…”
Section: Sex Differences In Cannabinoid Abusementioning
confidence: 94%